If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-2)+3x=-3(x+3)+21
We move all terms to the left:
6(x-2)+3x-(-3(x+3)+21)=0
We add all the numbers together, and all the variables
3x+6(x-2)-(-3(x+3)+21)=0
We multiply parentheses
3x+6x-(-3(x+3)+21)-12=0
We calculate terms in parentheses: -(-3(x+3)+21), so:We add all the numbers together, and all the variables
-3(x+3)+21
We multiply parentheses
-3x-9+21
We add all the numbers together, and all the variables
-3x+12
Back to the equation:
-(-3x+12)
9x-(-3x+12)-12=0
We get rid of parentheses
9x+3x-12-12=0
We add all the numbers together, and all the variables
12x-24=0
We move all terms containing x to the left, all other terms to the right
12x=24
x=24/12
x=2
| 9+4x=7+3x | | 0=-67/8x+313.5 | | 22+166=16x | | (b+6)+(3b)=180 | | 5x+15=4x+15 | | 20x=24x=16 | | 7=a/7−5 | | −11+6x=11x+4 | | (7,-6);m=(1/2 | | 3/4(x+12)-7=38 | | −14=−11+n/5 | | 4+12x=81 | | 6/15=x+1/40 | | 7a-6=9+2a | | -3(3p+5)-2(1-11p)-3(8+4p)=0 | | 0.25x+14=x | | 4(4–4k)=–10–16k | | {5}{7}(x-9)=25 | | 8w−8−6w=4w−7 | | –9+5k=6k | | k+113=180 | | 8w-8=40 | | 3c+12=10 | | x+(-4)=6.3 | | d/3=10=-2 | | ¾(x+12)-7=38 | | 4x+12x=81 | | 21/m=28/32 | | 8x-5+x=57 | | 4x-2+x=-7+2x | | -3(2x-1)=9x | | (5b+6)+(4b-6)=180 |